PENERAPAN MODEL PEMBELAJARAN CREATIVE ART UNTUK MENGEMBANGKAN ASPEK SENI PADA ANAK USIA DINI DI RA RAUDHATUL ILMI STABAT - Khairuni Siregar (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This study aims to determine the development of early childhood talent in RA Raudhatul Ilmi through the Creative Art learning model. This research was conducted in RA Raudhatul Ilmi with 17 (seventeen) children, consisting of eight (8) boys and nine (9) girls. The benefit of this research is to develop aspects of art development in early childhood. The technique or research method used is classroom action research or also called class Action Research. The result of this research is that by applying the creative art learning model, it turns out that aspects of children's art development can be developed, on the grounds that all creative art activities require children to be creative and develop their artistic talent with fun.